GaPP2, a multicentre randomised controlled trial of the efficacy of gabapentin for the management of chronic pelvic pain in women: study protocol. Issue 1 (31st January 2018) - Vincent, Katy; Baranowski, Andrew; Bhattacharya, Siladitya; Birch, Judy; Cheong, Ying; Cregg, Roman; Daniels, Jane; Hewitt, Catherine A; Macfarlane, Gary J; Middleton, Lee; Szubert, Wojciech; Tracey, Irene; et al.
Abstract : Introduction: Chronic pelvic pain (CPP) affects more than 1 million UK women with associated healthcare costs of £158 million annually. Current evidence supporting interventions when no underlying pathology is identified is very limited and treatment is frequently inadequate. Gabapentin (a GABA analogue) is efficacious and often well tolerated in other chronic pain conditions. We have completed a successful pilot randomised controlled trial Gabapentin for Pelvic Pain 1 (GaPP1) and here describe the protocol for our definitive multicentre trial to assess the efficacy of gabapentin in the management of CPP in women Gabapentin for Pelvic Pain 2 (GaPP2). Methods and analysis: We plan to perform a double-blind placebo-controlled randomised multicentre clinical trial, recruiting 300 women with CPP from up to 40 National Health Service hospitals within the UK. After randomisation, women will titrate their medication (gabapentin or placebo) over a 4-week period to a maximum of 2700 mg or placebo equivalent and will then maintain a stable dose for a 12-week period. Response to treatment will be monitored with validated questionnaires and coprimary outcome measures of average and worst pain scores will be employed. The primary objective is to test the hypothesis that treatment with gabapentin has the potential to provide an effective oral treatment to alleviate pain in women with CPP in the absence of any obvious pelvic pathology. Ethics and dissemination: Ethical approval has been obtained from the Coventry and Warwick Research Ethics Committee (REC 15/WM/0036). Data will be presented at international conferences and published in peer-reviewed journals. We will make the information obtained from the study available to the public through national bodies and charities. Trial registration number: ISRCTN77451762; Pre-results .